THE LUCAS-KANADE METHOD IMPLEMENTATION FOR ESTIMATING THE OBJECTS MOVEMENT IN THE MOBILE ROBOT’S WORKSPACE (Journal of Universal Science Research, 2024)
This article presents the Lucas-Kanade method implementation for estimating the objects movement in the mobile robot’s workspace using the Python programming language. The Lucas-Kanade method is used to calculate optical flow from sequential images and allows the motion of objects to be estimated. The necessary mathematical expressions are considered. As part of the study, experiments were conducted with different lighting levels to evaluate the robotic ability of the method under changing lighting conditions.